The Application of Slow Sand Filtration Technology for Improving Water Quality at Taman Gading Housing Area, Kaliwates District, Jember - Muflihah, Yeni Maulidah; Utomo, Denny Trias; Handayani, Wuryanti; Sulistiyo, Yudi Aris; Andarini, Novita; Asnawati, Asnawati; Indarti, Dwi (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
Water is a basic need for all living organisms. Water quality implies living quality. Several parameters influencing water quality include minerals, dissolved organic substances, and turbidity. The water consumed must meet proven water quality standards. However, water quality still needs to be improved in several areas before consumption. The well water in residential areas placed on rice fields generally needs to meet the requirements for consumption. Many Taman Gading housing complex residents, especially in RW 036 RT 006, still use the well water to meet their daily needs. The well water quality in this area tends to be smelly and somewhat misty. Proper treatment is needed to improve the quality of well water in this area to reduce the negative impact on the population's health in the long term. This training focused on well water purification and filtration using slow sand filtration technology (SPL) to improve water quality. This method uses activated charcoal, sand, gauze, and pumice as filter media in specific proportions. The use of this method is effective and efficient in reducing the turbidity level of the sample water to the threshold for drinking water (<500 ppm), with a neutral pH (close to 7.00). This technology is effortless for residents to use and apply independently at a relatively low cost.